PHYSIOLOGICAL BASIS OF PHYSICAL EXERCISES USED IN THERAPEUTIC PHYSICAL EDUCATION - Yakubova Guyoxon Kuchkarovna (Journals Park Publishing, 2025)
This article provides information on how physical exercises can be used to treat and prevent various diseases in the growing generation. Additionally, therapeutic physical education involves the conduction of exercises aimed at general stimulation of the patient, which improves the transmission of sensory and motor impulses, enhances the blood supply to the affected area, strengthens weakened muscles, and helps to relax contracted muscles.
Keywords: Therapeutic physical education, diseases of the nervous system, therapeutic physical exercises, physiological characteristics of physical exercises, nervous system diseases and injuries, trophic effect of physical exercises.